Detection of hemodynamic changes in a porcine lipopolysaccharide model of systemic inflammation using dynamic light scattering measurements of the microcirculation - te Nijenhuis, Louwrina H.; Gangaram-Panday, Norani H.; Specht, Patricia A. C.; Fine, Ilya; Elstein, Nimrod; Mik, Egbert G.; Harms, Floor A.; Reiss, Irwin K. M.; van Weteringen, Willem (Frontiers in Medicine, 2025)
BackgroundThe microcirculation is affected during sepsis, yet there is currently no clinically available technology for sepsis detection in the microcirculation. This study aimed to detect microcirculatory changes using a dynamic light scattering (DLS) skin sensor during an endotoxic shock with a systemic inflammatory response in a porcine lipopolysaccharide (LPS) model.MethodsThirty female Yorkshire x Norwegian Landrace pigs were divided into three groups: control, LPS, and LPS with resuscitation. After baseline measurements, LPS (1.75 μg∙kg−1∙h−1) was administered in progressively increasing dosages in the LPS and resuscitation groups. Two mDLS™ sensors, placed centrally and peripherally, measured total blood flow (TBF), relative blood velocity (RBV), and relative hemodynamic indices (relHIs) 1 h before (T0) and 1, 2, and 3 h after LPS administration (T1, T2, and T3). New DLS parameters describing heart rate variability (high-and low-frequency components HF and LF) and self-similarity (the Hurst exponent) were calculated.ResultsNo differences in TBF, RBV, and HF values were seen between the study groups after LPS administration. LF was peripherally higher at T2 in subjects receiving LPS than in controls. RelHIs showed a change in blood distribution between T0 and T1 in the resuscitation group. Both intervention groups showed a Hurst exponent decrease centrally at T2 and peripherally already at T1.ConclusionChanges in microcirculatory parameters, relHIs, and the Hurst exponent, were recorded for 3 h following LPS administration. The Hurst exponent was significantly lower in the LPS and LPS with resuscitation groups than in controls. Further clinical studies are required to determine the sensitivity and specificity of the non-invasive mDLS™ sensor for sepsis detection.